Pengaruh Profitabilitas, Solvabilitas, Likuiditas dan Ukuran Perusahaan Terhadap Nilai Perusahaan Masa Invasi Rusia dan Ukraina Pada Perusahaan Sub Sektor Indonesia (BEI) Periode 2019-2023 Food and Beverage Yang Terdaftar di BEI 2022-2023 - Maria Adriana Irama Koli; Maria P. L. Muga; Novi Theresia Kiak (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This research aims to examine the influence of profitability, solvency, liquidity and company size on company value during the invasion of Russia and Ukraine in sub-sector companies food and beverage listed on the Indonesia Stock Exchange for the 2022-2023 period. The population in this research is sub-sector companies food and beverage listed on the Indonesia Stock Exchange for the 2022-2023 period. The research sample was 25 sub-sector companies food and beverage obtained by technique purposive sampling. The data collection technique used is library research. Data analysis was carried out using multiple linear regression analysis. The research results show that partially profitability and solvency have a significant effect on company value. Furthermore, liquidity and company size have no effect on company value. The variables profitability, solvency, liquidity and company size simultaneously influence company value. The variables profitability, solvency, liquidity and company size in this study can explain company value during the Russian and Ukrainian invasion of sub-sector companies food and beverage which is listed on the Indonesia Stock Exchange for the 2022-2023 period with a value of R square amounting to 49.4%.